EFFECTIVE STRATEGIES IN TEACHING CHARACTER EDUCATION IN THE 2013 CURRICULUM - Ahmad Khanali; Hendra Susanto (International Journal of Teaching and Learning, 2025)
This literature research aims to identify and analyze effective strategies in teaching character education in the 2013 Curriculum. Character education is a fundamental element that aims to form students who are not only academically intelligent, but also have strong character. Various relevant literature was reviewed to reveal the best approach in implementing character education in a formal education environment. The results of the study show that effective strategies include the integration of character values into all subjects, the use of interactive learning methods, and the important role of teachers as role models. Apart from that, a supportive learning environment, involvement of parents and the community, use of technology, as well as holistic and diverse evaluation methods are also crucial aspects. Applying these strategies consistently and collaboratively can increase the effectiveness of character education teaching, in line with the objectives of the 2013 Curriculum to form a young generation who are competent and have good character.